A framework for analysing the effects of new, potentially disruptive technology on a business model case – Bluetooth. (7th September 2004) - Sainio, Liisa-Maija
This paper presents a framework for analysing the effects of a new, potentially disruptive technology on a firm's business model using Bluetooth technology and its possible effects on an operator's business model as an exploratory case example. The theoretical section discusses the classifications of new technologies and the conceptual relationships between such concepts as disruptive technologies and discontinuous innovations. The different definitions of the concept of business model are presented and the concept is set into the context of the resource-based view of the firm with modifications. The propositional framework is used to estimate both the disruptiveness potential of a new technology and the strategic importance of a new technology, both of which determine the possible amount of radical changes in a firm's business model.